Serum IGFBP-2 in systemic sclerosis as a prognostic factor of lung dysfunction - Julien Guiot; Makon-Sébastien Njock; Béatrice André; Fanny Gester; Monique Henket; Dominique de Seny; Catherine Moermans; Michel G. Malaise; Renaud Louis (Scientific Reports, 2021)
Abstract Systemic sclerosis (SSc) is a rare connective tissue disease associated with rapid evolving interstitial lung disease (ILD), driving its mortality. Specific biomarkers associated with the progression of this lung disease are highly needed. We aimed to identify specific biomarkers of SSc-ILD to predict the evolution of the disease. For this, we compared prospectively serum levels of several biomarkers associated with lung fibrosis in SSc patients (n = 102), among which SSc-no ILD (n = 63) and SSc-ILD (n = 39), compared to healthy subjects (HS) (n = 39). We also performed a longitudinal study in a subgroup of 28 patients analyzing biomarkers variations and pulmonary function tests over a period of 2 years. Serum level of IGFBP-2 was significantly increased in SSc patients compared to HS, and negatively correlated with pulmonary function (assessed by carbon monoxide transfer coefficient (KCO)) (r = − 0.29, p < 0.01). Two-year longitudinal analysis in a subgroup of 28 SSc patients determined that IGFBP-2 variation was positively correlated with KCO at 2-year follow-up (r = 0.6, p < 0.001). SSc patients with a lower variation of IGFBP-2 (less than 22%) presented significant deterioration of pulmonary function at 2-year follow-up (p < 0.01). ROC curve analysis enabled us to identify that baseline IGFBP-2 > 105 ng/ml was associated with a poor outcome (KCO < 70% predicted) at 2-year follow-up (AUC = 0.75, p < 0.05). We showed for the first time that serum levels of IGFBP-2 might be a prognostic factor of the development of SSc-ILD.